-3(x-7)+9x=6x+11

Simple and best practice solution for -3(x-7)+9x=6x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-7)+9x=6x+11 equation:


Simplifying
-3(x + -7) + 9x = 6x + 11

Reorder the terms:
-3(-7 + x) + 9x = 6x + 11
(-7 * -3 + x * -3) + 9x = 6x + 11
(21 + -3x) + 9x = 6x + 11

Combine like terms: -3x + 9x = 6x
21 + 6x = 6x + 11

Reorder the terms:
21 + 6x = 11 + 6x

Add '-6x' to each side of the equation.
21 + 6x + -6x = 11 + 6x + -6x

Combine like terms: 6x + -6x = 0
21 + 0 = 11 + 6x + -6x
21 = 11 + 6x + -6x

Combine like terms: 6x + -6x = 0
21 = 11 + 0
21 = 11

Solving
21 = 11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4(6-y)+10=-10(y-2)-9 | | 3v+v-3v=9 | | 5=7-9 | | 8.425-3.143x=9.214x+12.081 | | a+7=-14 | | -42x-12=-6(6x-4) | | -13=12+m | | c=3+-3 | | -1+n=-20 | | -11x+10=-12x+8 | | 9x+3y+1y-0.9x= | | 10y-17=6y-12 | | -6x-10=38 | | 9x^2+18x-39=0 | | -10=h-6 | | -9+13x=11-x | | 5.39x+16=29.0521+4x | | 11-5x+3=2x+4-3x | | -13m+14-11=7(-m+13)+2 | | 15x+2=9x+22 | | 7(7y+17)=16+8(5y+5) | | 4x^5-22x^3-80x=0 | | -6p+7=-5(2p+13) | | 10(2)-3x=15 | | -16w=8(-w+6) | | r^2-2r^2+3r^2= | | (2dc)(4c^2d^5)= | | -20j+3j+19=-9(3j+18)-19 | | 10(0)-3x=15 | | 7(-r-15)+9r=9r | | (3x-3)*2x=84 | | 5(-b+4)=-(20-5b) |

Equations solver categories